2021
DOI: 10.1097/qad.0000000000002975
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papilloma virus, precancerous lesions and cancer in anal condylomas

Abstract: Introduction: Anal condylomas are associated with human papillomavirus (HPV) infection and are a risk factor for anal squamous cell carcinoma (SCC).Objective: To conduct a meta-analysis evaluating the prevalence of anal high-risk HPV, high-grade squamous intraepithelial lesions (HSIL) and SCC in patients with condylomas. The standardized incidence ratio (SIR) and the incidence rate of anal SCC were also calculated.Methods: Three electronic databases were searched until April 2020. Meta-analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…8 The overall incidence rate of anal SCC in these patients was 7 per 100,000 person-years and was higher in men (13 per 100,000 person-years) than in women (5 per 100,000 person-years). 8…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…8 The overall incidence rate of anal SCC in these patients was 7 per 100,000 person-years and was higher in men (13 per 100,000 person-years) than in women (5 per 100,000 person-years). 8…”
mentioning
confidence: 78%
“…A meta-analysis reported that the prevalence of anal HSIL in patients with anal condylomas was 24% in immunocompromised and 12% in nonimmunocompromised patients, with an OR of 2.5 (1.7-3.7, p < .001) for immunocompromised patients. 8 Compared with cervical HSIL, less information has been published on the progression rate of anal HSIL to cancer. A Danish study evaluated the risk of progression in 1222 individuals with anal intraepithelial neoplasia 3 (AIN3) identified at the Danish Pathology Registry.…”
Section: Epidemiology Of Anal Hpv and Anal Intraepithelial Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…37 Recommendations state that atypical lesions that do not respond or worsen during treatment or those with an uncertain diagnosis should be sent for histological analysis. 38 Condylomas have been considered benign lesions, but a recent meta-analysis by Albuquerque et al 39 showed that the prevalence of anal high-grade squamous intraepithelial lesions (HSILs) in anal condylomas from immunocompromised patients was 24.0% (16.4% À 33.7%), and high-risk HPV infection was present in 40.2% (21.0-63.1%) of these patients. Patients, especially men, with a history of anal condylomas have a high risk of anal SCC.…”
Section: Anal and Perianal Condylomasmentioning
confidence: 99%
“…The overall incidence rate of anal SCC in individuals with a history of anal condylomas was 6.5 per 100,000 person-years (3.6 À 11.7), 12.7 (9.1 À 17.8) in men and 4.7 (1.7 À 13) in women. 39 Perianal condylomas can be associated with intra-anal condylomas, and, when present, an evaluation of the anal canal with anoscopy might be needed. 40 Data from the Australian Study of the Prevention of Anal Cancer (SPANC), which included men who have sex with men (MSM) and bisexual men aged 35 years and older, showed that many of the patients with anal condylomas did not have a known history of this condition, suggesting that many were unaware of this diagnosis.…”
Section: Anal and Perianal Condylomasmentioning
confidence: 99%